2018
DOI: 10.1124/jpet.118.249102
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing SET Augments the Effects of Radiation Therapy in Hepatocellular Carcinoma through Reactivation of PP2A-Mediated Akt Downregulation

Abstract: Increasing evidence suggests that SET functions as an oncoprotein and promotes cancer survival and therapeutic resistance. However, whether SET affects radiation therapy (RT)-mediated anticancer effects has not yet been explored. We investigated the impact of SET on RT sensitivity in hepatocellular carcinoma (HCC). Using colony and hepatosphere formation assays, we found that RT-induced proliferative inhibition was critically associated with SET expression. We next tested a novel SET antagonist, N-(3-ethynylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…8b). Consistent with previous studies 51 , Akt activity (revealed by phosphorylation at T308 and S473) was greatly decreased upon SET inhibition in RKO cells (Fig. 8b).…”
Section: Resultssupporting
confidence: 92%
“…8b). Consistent with previous studies 51 , Akt activity (revealed by phosphorylation at T308 and S473) was greatly decreased upon SET inhibition in RKO cells (Fig. 8b).…”
Section: Resultssupporting
confidence: 92%
“…Mutations leading to the abnormal expression of PP2A scaffolds and regulatory subunits are common in many human cancers [16]. Therefore, based on its tumor suppressive properties, the reactivation of PP2A is a potential strategy for cancer treatment [17,18]. Targeting the oncoprotein CIP2A is an important strategy to reactivate PP2A to treat cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic role of SET in HCC was first suggested by Fukukawa et al [ 70 ] who demonstrated that SET expression is highly upregulated in progressive HCC, indicating that SET may be involved in HCC development. Furthermore, SET activity is associated with development of resistance to chemotherapies [ 71 , 72 , 73 ]. Results obtained with patient primary cells support the oncogenic role of SET in HCC, suggesting that SET may serve as a novel biomarker to guide treatment in patients with HCC [ 69 ].…”
Section: Discussionmentioning
confidence: 99%